Pengaruh Health Education Melalui Aplikasi Ikat TB terhadap Tugas Kesehatan Keluarga dalam Pencegahan dan Pengobatan TB Paru di Puskesmas Lamongan - Ayu Aisyah; Arifal Aris; Suhariyati Suhariyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Pulmonary tuberculosis (TB) remains a major public health concern in Indonesia. Active family involvement in both prevention and treatment is crucial; however, many families have yet to fulfill their health-related responsibilities effectively. This study aimed to evaluate the effect of health education through the IKAT TB (Tuberculosis Health Information) application on family health responsibilities in the prevention and treatment of pulmonary TB. A pre-experimental design with a one-group pretest-posttest approach was used. The sample consisted of 46 respondents selected through total sampling. The intervention involved providing education via the IKAT TB application, and data were collected using a family health responsibility questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed an increase in family health responsibility scores following the educational intervention. The Wilcoxon test produced a p-value of 0.000 (p < 0.05), indicating a significant difference between pre- and post-intervention scores. The findings suggest that health education delivered through the IKAT TB application is effective in enhancing family engagement in TB prevention and treatment. Digital media platforms such as mobile applications offer accessible information and can strengthen family involvement in TB care.